DVGs Mankutimmana Kagga: A Yokels Sheafs - D V Gundappa; GUNDAPPA (D V); NATARAJAN (K) Tr (Mysore DVG Balaga Prathisthana, 2024)
Mankutimmana Kagga is a resplendent jewel in the crown of Kannada Literature, with a tremendous reach. It sensitizes intellectual and emotive instincts of the reader. It exudes exquisite poetic beauty and a grandeur of philosophical thought. It is an amalgam of the virtues of surrender to God, celebration of life, catholicity of outlook and inclusivity. The reader will feel enlightened and elevated; his experience will be fulfilling.
Keywords: Indian English Poetry; Kannada Poetry Tr in English